Graduate employability and digital entrepreneurship in the era of IR 4.0 / Surina Nayan ... [et al.] - Nayan, Surina; Asmaak Shafie, Latisha; Chulan, Majdah; Zakaria, Fazmawati; Nayan, Suhaimi (Universiti Teknologi MARA, Perlis, 2021)
This is a conceptual paper on virtual entrepreneurship that can be ventured by graduates in Malaysia in the IR 4.0 era. The study defines what virtual entrepreneurship is, its advantages, reviews of some literature on the topic, IR 4.0 and its effects on Malaysian businesses in general. Besides, the paper also focuses on types of virtual entrepreneurship that Malaysian graduates can explore. They can venture into cyber-security analyst positions, can produce and innovate IoT tools and solutions, be online retail consigners, can be content creators for Instagram, Twitter and Facebook for companies that need their services, can do freelance copywriting and editing for new companies or traditional companies, can become social media influencers, can become YouTube personalities, can assume the role of digital strategy experts and they can also offer digitalized services and solutions. As a result, they will not depend a lot on working with the government or private sector. It is a well-known fact that getting a job in an office is difficult nowadays. They can find their income to continue supporting their lives in today's challenging world when they are aware of the opportunities offered to them using the virtual world. They can venture into areas that do not require them to commute to their offices every day. Instead, they can just work in front of their laptop or pc or tab which is connected to the internet. Furthermore, they can create other job opportunities for others.